Association of fat-soluble vitamins (A, D, and E) status with humoral immune response to COVID-19 inactivated vaccination - Deng, Yao; Huang, Liting; Liu, Peixin; Geng, Xuyang; Lin, Zefang; Zheng, Zhixiong; Zhan, Meixiao; Zhang, Zhiren; Liu, Junwei; Sun, Taoping (Frontiers in Nutrition, 2023)
Background: Fat-soluble vitamins (A, D, and E) are essential for the proper functioning of the immune system and are of central importance for infection risk in humans. Vitamins A, D, and E have been reported to be associated with the immune response following vaccination, however, their effects on the immune response to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) vaccination remain unknown. Methods: We measured the neutralizing antibody titres against wild type and Omicron within 98 days after the 3rd homologous boosting shot of inactivated SARS-CoV-2 vaccine (BBIBP-CorV or CoronaVac) in 141 healthy adults in the prospective, open-label study. High-performance liquid chromatography-tandem mass spectroscopy was used to determine the concentrations of plasma vitamins A, D, and E. Results: We found the anti-wide-type virus and anti-Omicron variant antibody levels significantly increased compared with baseline antibody levels (P < 0.001) after 3rd vaccination. 25(OH)D3 was significantly negatively associated with the baseline anti-wide-type virus antibody concentrations (beta (95% CI) = -0.331 (-0.659 -0.003) after adjusting for covariates. A potentially similar association was also observed on day 98 after the third vaccination (beta (95% CI) = -0.317 (-0.641 0.007)). After adjusting for covariates, we also found 25(OH)D3 significantly negatively associated with the seropositivity of anti-Omicron variant antibody at day 98 after 3rd vaccination (OR (95% CI) = 0.940 (0.883 0.996)). The associations between plasma 25(OH)D3 with anti-wild-type virus antibody levels and seropositivity of anti-Omicron variant antibodies were persistent in subgroup analyses. We observed no associations between retinol/α-tocopherol and anti-wide-type virus antibody levels or anti-Omicron variant antibody seropositive in our study. Conclusion: The 3rd inactivated SARS-CoV-2 vaccination significantly improved the ability of anti-SARS-CoV-2 infection in the human body. Higher vitamin D concentrations could significantly decrease the anti-wide-type virus neutralizing antibody titres and anti-Omicron variant antibody seropositive rate after the inactivated SARS-CoV-2 vaccination in people with adequate levels of vitamin D, better immune status, and stronger immune response; further studies comprising large cohorts of patients with different nutritional status are warranted to verify our results.